An Adaptation Level Theory of Tinnitus Audibility - Searchfield, Grant; Kobayashi, Kei; Sanders, Michael (Frontiers in Systems Neuroscience, 2012)
Models of tinnitus suggest roles for auditory, attention and emotional networks in tinnitus perception. A model of tinnitus audibility based on Helson’s (1964) Adaptation Level Theory (ALT) is hypothesized to explain the relationship between tinnitus audibility, personality, memory and attention. This theory attempts to describe how tinnitus audibility or detectability might change with experience and context. The basis of ALT and potential role of Auditory Scene Analysis in tinnitus perception are discussed. The proposed psychoacoustic model lends itself to incorporation into existing neurophysiological models of tinnitus perception. It is hoped that the ALT hypothesis will allow for greater empirical investigation of factors influencing tinnitus perception, such as attention and tinnitus sound therapies.